2016
DOI: 10.2298/fil1614689h
|View full text |Cite
|
Sign up to set email alerts
|

Signless Laplacian spectral characterization of graphs with isolated vertices

Abstract: A graph is said to be DQS if there is no other non-isomorphic graph with the same signless Laplacian spectrum. For a DQS graph G, we show that G ? rK1 is DQS under certain conditions. Applying these results, some DQS graphs with isolated vertices are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…✷ In [18], Cámara and Haemers proved that a graph obtained from K n by deleting a matching is DAS. In [36], it have been shown that this graph is also DQS. Remark 5 Some 3-regular DAS graphs are given in [31,43].…”
Section: Resultsmentioning
confidence: 92%
“…✷ In [18], Cámara and Haemers proved that a graph obtained from K n by deleting a matching is DAS. In [36], it have been shown that this graph is also DQS. Remark 5 Some 3-regular DAS graphs are given in [31,43].…”
Section: Resultsmentioning
confidence: 92%
“…The graph G p,n,q is determined by its Laplacian spectrum. Lemma 2.9 ( [20]). Let T be a DLS tree of order n. Then T ∪ rK 1 is DLS.…”
Section: Lemma 26 ([5]mentioning
confidence: 99%
“…In fact, only few graphs with special structures have been proved to be determined by their spectra. For some recent papers on this topic, see [8,18,20,24,30]. As usual, P n , C n , S n and K n stand for the path, the cycle, the star graph and the complete graph of order n, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the path, the complement of a path, the complete graph, and the cycle were proved to be determined by their adjacency spectra [6,9]. The path, the complete graph, the cycle, the star and some quasi-star graphs, together with their complement graphs were shown to be determined by their Laplacian spectra [6,9,15,21]. Let K m n be the graph obtained by attaching m pendant vertices to a vertex of the complete graph K n−m , and U n,p be the graph obtained by attaching n − p pendant vertices to a vertex of C p .…”
mentioning
confidence: 99%